A bioinspired piezocomposite propulsor: An electromechanical model. (January 2021) - Shan, Xin; Bilgen, Onur
This article presents an experimentally validated electromechanical beam model for a representative cymbal-like piezocomposite active segment of a bioinspired piezocomposite aquatic propulsor/pump. The proposed concept is a self-contained propulsion/pumping system involving a series of piezoactive soft cymbal-like segments that are connected by passive soft connective segments. A series of phased excitations in expansion and contraction applied to active segments create a traveling wave along the axis of the pump, which in return propels the fluid. A parametric analysis is conducted using the proposed model to understand the effectiveness of the cymbal-like piezocomposite active segment as a function of critical structural parameters. Area change of the cymbal-like actuators, which is correlated to the propulsion power, is studied based on the analysis of the induced moment, curvature, and area change due to piezoelectric excitation. Objective functions and criteria are proposed and evaluated to understand the effectiveness, and to identify the optimal structural parameters of the piezocomposite pump. The influence of a sealant layer for waterproofing is also examined. Both bimorph and unimorph configurations are analyzed, and the results are compared.